Viabilidade e segurança do transplante intratecal de células-tronco mesenquimais autólogas e alogênicas provenientes da medula óssea de cães (lupus canis familiaris) - Benavides, Felipe Pérez [UNESP] (2013)
The study aimed to evaluate clinical and laboratory viability and safety of intrathecal transplantation of bone marrow mesenchymal stem cells (BM-MSC) autologous and allogeneic of dogs. A total of 15 dogs, mixed breed, adults of both sexes, clinically healthy, except two who had chronic spinal trauma. They were divided into three groups with five animals each. BM-MSC were obtained by puncture of the bone marrow, isolated and cultured. Group A was transplanted with autologous BM-MSC intrathecally via the cisterna magna, while group B received allogenic BM-MSC and group C (control) was administered phosphate buffered saline (PBS). Cerebrospinal fluid (CSF) was obtained immediately before transplantation of BM-MSC (moment 1) and the fifth day after (moment 2) for physico-chemical, cytological and the concentration of matrix metalloproteinases (MMP-2 and MMP-9 .) All Animals were monitored by neurological examination before and after transplantation. By clinical and laboratory evaluations, no significant changes were observed after transplantation of BM-MSC autologous and allogeneic intrathecal, proving to be a safe and viable for the use of cell therapy in dogs